Learning by doing and academic performance in Business Administration students - Cortés Bracho, Oriana; Betancourt Rodriguez, Libnazaret; Mejía Turizo, Jorge; Ojeda Beltrán , Adelaida del Carmen; Cortés Bracho, Oriana; Betancourt Rodriguez, Libnazaret; Mejía Turizo, Jorge; Ojeda Beltrán , Adelaida del Carmen; Cortés Bracho, Oriana; Betancourt Rodriguez, Libnazaret; Mejía Turizo, Jorge; Ojeda Beltrán , Adelaida del Carmen (Corporación Universitaria Americana, 2023)
Introduction: Traditional education in the classroom has been questioned in its ability to respond to the needs of the knowledge society, so the center of the discussion is directed to the change of methodologies that are more suitable and coherent with the environment, such as the learning by doing methodology, expressed as experiential learning that forces the student to solve problems outside the classroom. Objective: The objective of this article is to analyze how the Learning by Doing methodology is related to the academic performance of business administration students. Methodology: the comparison of the final grades of two groups of students is proposed: group A made up of a sample of 34 students (control group that took the subject in the first semester of 2022, in the traditional way) and group B (experimental group that took the subject in the second semester of 2022 under the aforementioned methodology) made up of a sample of 29 students. Likewise, group B was measured at two moments (before and after having participated in learning by doing activities) with a pre and post test. Results: The results showed an improvement in the grades of group B, additionally an improvement in leadership, innovation and creativity skills was observed in the students of this group. Conclusions: This research highlights the need to adopt methodologies such as learning by doing in the training of business administrators.